Teacher Becoming Curriculum Designer: Professional Teaching and Learning in China’s Early Childhood Education - Tian, Xiaoming; Bao, Li; Li, Tianxin; Gu, Yue (Frontiers in Psychology, 2022)
The Curriculum Design Coherence Model (CDC Model) was created as a universal curriculum design method to connect disciplinary knowledge to teachers’ expertise in a bid to promote professional teaching and learning. However, research into how the CDC Model has been adopted and localized in the Chinese educational context is scarce. This article focuses on the application and impact of the CDC Model on the resulting teaching practices in China’s Early Childhood Education (ECE) settings. The data collected through a focus group discussion with 21 teachers from a model kindergarten at the municipal level in China reveals that the CDC Model has increased the teachers’ professionalism by promoting their curriculum initiative, forging curriculum knowledge orientation, strengthening the conceptual structure within the kindergarten-developed curriculum, and enhancing the coordination between the curricula of the different courses offered by the kindergarten. This positive influence has also helped the teachers bridge their disagreement on curriculum content and pedagogy and overcome some difficulties in using the CDC Model. The study has implications for revitalizing the value of disciplinary knowledge and for viewing ECE teachers as active professional agents in ECE curriculum design and teaching.